Bovine abortion-related Streptococcus pluranimalium: a microbiological, pathological and molecular diagnostic approaches - Rafaela da Rosa Marques; Mariana Costa Torres; Eryca Ceolin Lamego; Milena Carolina Paz; Saulo Petinatti Pavarini; Franciele Maboni Siqueira (Ciência Rural, 2025)
ABSTRACT: Considering the relevance of differential diagnosis in identifying the cause of abortions in cattle, this study described a case of bovine abortion caused by Streptococcus pluranimalium. A bovine abortion with external characteristics compatible with eight months of gestation and the corresponding placenta was submitted to pathological evaluation. On external examination, the fetus measured 58 cm from the rostral portion of the head to the insertion of the tail, a smaller size than expected for the gestational age, and had a low body condition score. Macroscopically, the lesions were restricted to the placenta characterized by hyperemia and intense fibrin deposition. Histological lesions consisted of marked multifocal necrosuppurative placentitis, with multifocal fibrinoid vasculitis, in addition to microthrombosis in alveolar capillaries and discrete alveolar infiltrate of intact and degenerated neutrophils. Bacterial culture of lung and placental samples revealed isolation of Streptococcus sp. The bacterial isolate was identified as S. pluranimalium based on mass spectrometry (MALDI-TOF MS). The in vitro antimicrobial susceptibility profile of the identified bacteria was evaluated by the agar disk diffusion method, showing sensitivity to all antimicrobials tested. Confirmation of the identity and phylogenetic profile of the isolate was performed by amplification of the 16S-rDNA gene and Sanger sequencing. The present report studied the microbiological, histopathological, and molecular aspects of S. Pluranimalium as a uncommon primary agent of bovine.